Kajian Hermeneutik Terhadap Makna Kebahagiaan Menurut Mazmur 1:1-6 Dan Relevansinya Bagi Kehidupan Pemuda - Suoth, Philia Sifra; Suoth, Vanny Nancy (Educatio Christi, 2024)
This article attempts to discuss how as a young person to interpret the text of Psalm 1:1-6, the aim is to reveal the meaning contained in the text. By using very unique and different figurative language, as well as to achieve relevance for the lives of the youth of the GMIM Walinouw Tumaluntung congregation, Minawerot One Region. In carrying out the research, the methods used were historical critical and qualitative hermeneutical methods. The results of this research speak to the meaning of happiness and the application of the appropriate relevance of happiness to the lives of the youth of the GMIM Walinouw Tumaluntung congregation in the Minawerot Satu Region as a form of gratitude to God who is extraordinary for his people and our form of repaying everything that God has given us.